2021
DOI: 10.12688/f1000research.28178.2
|View full text |Cite
|
Sign up to set email alerts
|

Perception on Online Teaching and Learning Among Health Sciences Students in Higher Education Institutions during the COVID-19 Lockdown – Ways to Improve Teaching and Learning in Saudi Colleges and Universities

Abstract: Background: Online learning or E-learning are approaches to broadcasting teaching by the means of internet technology and software applications. Kingdom of Saudi Arabia is likewise embarking on the rapid growth in online education. The purpose of this study is to investigate the student’s perceptions regarding online teaching and learning during COVID 19. Methods: An online computer-based cross-sectional study was conducted between May and June 2020. A pre-validated questionnaire was used and administrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Student anxiety levels during the sudden shift to online learning moderately influenced student perceptions of independence and responsibility in their learning as well as learning goal achievement (Almoayad et al, 2020). In another study in Saudi Arabia, among 281 health science students, overall 62% of the students expressed their satisfaction with online learning (Aziz Ansari et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student anxiety levels during the sudden shift to online learning moderately influenced student perceptions of independence and responsibility in their learning as well as learning goal achievement (Almoayad et al, 2020). In another study in Saudi Arabia, among 281 health science students, overall 62% of the students expressed their satisfaction with online learning (Aziz Ansari et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Saudi Arabia, most universities have recently adopted e-learning choices in their educational activities ( Muhammad et al, 2020 ). According to Ansari et al (2021) , e-learning choices in educational activities were not common among educational institutes. However, after the COVID-19 pandemic, all Saudi institutions began using e-learning systems and platforms to continue delivering educational content to students.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was conducted to evaluate the satisfaction of the students of Ghaen and Ferdows medical schools with virtual education and the factors affecting this satisfaction during the COVID-19 pandemic. The findings of this study showed that in the critical conditions of the COVID-19 pandemic, the academic satisfaction of most (15). In the latter investigation, the quick response of professors to the questions of students, readiness to give lectures, and online communication between professors and students were some of the positive points reported by students.…”
Section: Discussionmentioning
confidence: 54%